Pengaruh Trichokompos terhadap Kadar P dari Kelopak Bunga Rosella (Hibiscus sabdariffa) pada Tanah Ultisol - Surya Wiatara Zebaoth; Muhammad Noor (Universitas Lambung Mangkurat, 2026)
This research aims to determine the effect of trichocompost application on phosphorus (P) levels in rosella (Hibiscus sabdariffa) flower petals planted in ultisol soil and determine the best dose that supports growth and flower production. The research was carried out in June–September 2024 at the Animal Husbandry Lecturer's Experimental Field, Banjarbaru, with soil analysis at the Laboratory of the Banjarbaru Center for Standardization and Industrial Services and the Agroecotechnology Laboratory of Lambung Mangkurat University. The research design used a one-factor Randomized Block Design (RAK) with four trichocompost dosage levels, namely 20 t/ha, 25 t/ha, 30 t/ha, and 35 t/ha, each repeated six times so that there were 24 experimental units. The results showed that the application of trichocompost had a significant effect on the efficiency of P uptake and the production of rosella flower petals. The dose of 30 t/ha produced the highest absorption efficiency of 51.2%, while the dose of 20 t/ha and 25 t/ha was only around 13–14%, and the dose of 35 t/ha decreased to 27.4%. The highest petal dry weight was also obtained at a dose of 30 t/ha of 4.94 g/sample, higher than 20 t/ha (0.67 g), 25 t/ha (1.15 g), and 35 t/ha (3.96 g). Thus, a dose of 30,85 is the most optimal condition in increasing P availability and rosella biomass production in ultisol soil.